The moonstone - Collins, Wilkie (Oxford University Press, 2010)
Content: The Moonstone is a beautiful yellow diamond that was stolen from the statue of a Moon god in India. When Franklin Blake brings it to Rachel Verinder's house in Yorkshire for her birthday, it brings bad luck with it. How many people will the Moonstone hurt? How many must die before the diamond's revenge is complete?